Analysis of Falling Ball under the Influence of Gravity using MSC Adams - Dr. H M Naveen (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The paper focusses on the analysis of falling ball from a certain height under the influence of gravity. The analysis includes study of displacement, velocity and acceleration of the falling ball. The study is carried out in MSC Adams software. This includes mechanical modelling of the system, setting the initial conditions and simulating the model to understand the characteristics. Verification of the model is also carried out.
Keywords: Analysis; Falling Ball; MSC Adams